Intellectual Capital: A Competitive Asset for Driving Innovation in Engineering Design Firms - Yitman, İbrahim (American Society for Engineering Management, 2011)
Intellectual Capital (IC) is recognized as a key strategic asset for organizational performance, and innovative solutions and its management is critical for the competitiveness of organizations. The aim of this article is to analyze the relationships among intellectual capital, competitiveness, and innovation drivers in engineering design firms of the Turkish construction industry. The research involves a questionnaire survey administered to engineering firms on intellectual capital constructs, competitiveness, and innovation drivers in construction. The article provides details on how firms can leverage their intellectual capital as the main competitive asset for innovative solutions to offer their clients.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1080/10429247.2011.11431891) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Intellectual Capital; Competitiveness; Innovation Drivers; Engineering Design Firms; Construction